Criptosporidiose em animais domésticos: aspectos epidemiológicos - Saraiva Bresciani, Katia Denise [UNESP]; Costa de Aquino, Monally Conceicao [UNESP]; Zucatto, Anaiza Simao [UNESP]; Inacio, Sandra Valeria [UNESP]; Silveira Neto, Luiz da [UNESP]; Dourado Coelho, Natalia Marinho [UNESP]; Dourado Coelho, Willian Marinho [UNESP]; Lemos de Brito, Roberta Lomonte [UNESP]; Viol, Milena Arauz [UNESP]; Meireles, Marcelo Vasconcelos [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
Studies related cryptosporidiosis will be essential, due to its relevance in public health and pathogenicity in pets and production animals. Over the past 20 years, there has been a rapid expansion of research involving the Cryptosporidium genus, largely related to molecular studies, providing a description of various species, genotypes and subtypes of the parasite. The molecular characterization of isolates from different sources (human, animal and environmental) has been widely used in order to investigate the potential zoonotic of this protozoa. The documented transmission forms from animals to humans, from person to person, through water intake or water for the leisure that are directly or indirectly contaminated with sporulated oocysts. The high rate of animals naturally infected and the susceptibility by protozoan, justify the importance of attending to the occurrence of this disease. So are demonstrated epidemiological aspects of this zoonotic disease in domestic animals.
Cryptosporidiosis in livestock and pets: epidemiological aspects
Keywords: Cryptosporidium spp.; ruminants; horses; dogs; cats